Smolnytska O. Narcissistic Perversion in Reliance on the Characters in the Selected Works of Classical and Contemporary Literature: Psychoanalytic Aspect - Olga Smolnytska (Philological Treatises, 2020)
Narcissism as a multifaceted problem is studied in contemporary Ukrainian literary studies, including in psychoanalytic works devoted to philology. In particular, it is a project of the psychohistory of the Ukrainian literature proposed by Nila Zborovska. But the problem of narcissistic perversion, which is becoming more and more relevant in modern times, has not yet been isolated in literary criticism. Instead, fiction is an example of a clear depiction of such a problem in the images of imitators, egocentric manipulators, the display of unhealthy (sick) relationships etc. The main features of the perverse narcissist are singled out in the article. At the same time, manifolds and greater breadth of this type were found in the example of fiction (as opposed to the regularities in accessible psychoanalytic studies). The examples of hysteria and hysteroidism in reliance on the heroines of Lessya Ukrainka are considered, compared with the image of Lisa Khokhlakova in the novel by F. Dostoevsky “The Brothers Karamazov”. The paralyzed Ukrainianity and paralyzed Christianity in the feminine version are singled out. It is found that the absence of sublimation (in relation on Nerisa) leads to loss of moral qualities. The research emphasizes on the national identity (Nerisa vs Euphrosyne and Antaeus). The characters of Nerisa (“Orgy” by Lessya Ukrainka) and Salome (O. Wilde) are compared. The Lady Macbeth syndrome was identified as one of the signs of perverse narcissus. On the basis of the analyzed texts, there are extracted some binary oppositions, such as: sacred/profane, introvert/extravert, spiritual/fleshly, up(top)/low, creativity/imitation, Eros/Thanatos. Methods of research: comparative, Jungian (analytical psychology), translation studies, mythological, intermedial. For a clearer understanding of the clinical picture of feminine characters, the historical context is presented. The material of the analysis is artistic literature and opinion journalism (epistolary texts). Attention is paid to the texts of the Ukrainian, British, American, Austrian, Russian literatures, as well as folklore and mythology of different nations.